Anti-Thrombin and its Biological Significance - Umer Saeed Ansari (Pakistan Journal of Medical & Health Sciences, 2023)
Anti-thrombin (AT) is a small molecular weight glycoprotein molecule, synthesized by liver, and circulates in the plasma at a concentration approximately 150 mg/ml1. AT belongs to a family of serine proteases, and most potent inhibitor of coagulation, and has vital role in maintaining haemostatic balance. It is also termed as ‘Heparin Cofactor’, and is considered essential for effective heparin therapy. Under normal conditions, its biological half-life is 1.5–2.5 days; But in conditions of acquired deficiency, and in the presence of heparin, the half-life of AT is much shorter, even being reduced to few hours.